A Mini Review on the Cold Flow Properties of Biodiesel and its Blends - Hazrat, M. A.; Rasul, M. G.; Mofijur, M.; Khan, M. M. K.; Djavanroodi, F.; Azad, A. K.; Bhuiya, M. M. K.; Silitonga, A.S. (Frontiers in Energy Research, 2020)
Biodiesels are renewable fuel that may be produced from various feedstock using different techniques. It is endorsed in some countries of the world as a viable substitute to diesel fuel. While biodiesel possesses numerous benefits, the cold flow properties (CFP) of biodiesel in comparison with petro-diesel are significantly less satisfactory. This is due to the presence of saturated and unsaturated fatty acid esters. The poor CFP of biodiesel subsequently affects performance in cold weather and damages the engine fuel system, as well as chokes the fuel filter, fuel inlet lines, and injector nozzle. Previously, attempts were made to minimize the damaging impact of bad cold flow through the reduction of pour point, cloud point, and the cold filter plugging point of biodiesel. This study is focused on the biodiesel CFP-related mechanisms and highlights the factors that initialize and pace the crystallization process. This review indicates that the CFP of biodiesel fuel can be improved by utilizing different techniques. Winterisation of some biodiesel has been shown to improve CFP significantly. Additives such as polymethyl acrylate improved CFP by 3-9 ° C. However, it is recommended that improvement methods in terms of fuel properties and efficiency should be carefully studied and tested before being implemented in industrial applications as this might impact biodiesel yield, cetane number, etc.